Comparison of saliva with oral and nasopharyngeal swabs for SARS‐CoV‐2 detection on various commercial and laboratory‐developed assays. Issue 9 (3rd May 2021) - Labbé, Annie‐Claude; Benoit, Patrick; Gobeille Paré, Sarah; Coutlée, François; Lévesque, Simon; Bestman‐Smith, Julie; Dumaresq, Jeannot; Lavallée, Christian; Houle, Claudia; Martin, Philippe; Mak, Anton; Gervais, Philippe; et al.
Abstract: The accurate laboratory detection of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is a crucial element in the fight against coronavirus disease 2019 (COVID‐19). Reverse transcription‐polymerase chain reaction testing on combined oral and nasopharyngeal swab (ONPS) suffers from several limitations, including the need for qualified personnel, the discomfort caused by invasive nasopharyngeal sample collection, and the possibility of swab and transport media shortage. Testing on saliva would represent an advancement. The aim of this study was to compare the concordance between saliva samples and ONPS for the detection of SARS‐CoV‐2 on various commercial and laboratory‐developed tests (LDT). Individuals were recruited from eight institutions in Quebec, Canada, if they had SARS‐CoV‐2 RNA detected on a recently collected ONPS, and accepted to provide another ONPS, paired with saliva. Assays available in the different laboratories (Abbott RealTime SARS‐CoV‐2, Cobas® SARS‐CoV‐2, Simplexa™ COVID‐19 Direct, Allplex™ 2019‐nCoV, RIDA®GENE SARS‐CoV‐2, and an LDT preceded by three different extraction methods) were used to determine the concordance between saliva and ONPS results. Overall, 320 tests were run from a total of 125 saliva and ONPS sample pairs. All assays yielded similar sensitivity when saliva was compared to ONPS, with the exception of one LDT (67% vs. 93%). The mean difference in cycle threshold (∆ C t ) was generally (but not significantly) in favor of the ONPS for all nucleic acid amplification tests. The maximum mean ∆​​​​​ C t was 2.0, while individual ∆ C t varied importantly from −17.5 to 12.4. Saliva seems to be associated with sensitivity similar to ONPS for the detection of SARS‐CoV‐2 by various assays. Highlights: Shortage of trained staff and sampling material calls for alternative, ideally non‐invasive, sampling methods We analysed and compared the ONPS and saliva paired specimens collected from 125 individuals who had SARS‐CoV‐2 RNA detected on another recently collected ONPS. All commercial assays yielded similar sensitivity when saliva was compared to ONPS. However, mean difference in cycle threshold was generally in favor of the ONPS for all assays, with important individual variability. Saliva sampling offers a suitable alternative to swab sampling in a context of sampling material shortage